How Is E-Government Readiness and Its Impact On Muhammadiyah Citizens? (An Analysis of Ponorogo Internet Program Enters RT) - Dian Suluh Kusuma Dewi; Dwiana Binti Yulianti; Ekapti Wahjuni Djuwitaningsih (Journal of Government and Civil Society, 2024)
In today's digital age, the internet is a crucial necessity. There are now more digital-based tasks than manual ones. Local governance as it is currently practiced is based entirely on digital technology. The Internet enters RT program was developed to advance the Ponorogo community's human resources. This article examines the e-government's readiness to administer the Internet enters RT program and explores how it has affected Muhammadiyah members in Ponorogo. The quantitative approach was employed in the conduct of this study. The Ponorogo Muhammadiyah community received the questionnaire. Data were processed using PLS SEM and descriptive quantitative analysis was performed. The study's findings demonstrate that 95% of e-government readiness has already been achieved, specifically in the areas of ICT infrastructure, law and regulations, social environment, managerial work, leadership, workforce competencies, and information security. By realizing e-government readiness in the Internet enters RT program, it encourages public trust. The public's trust in e-government serves as the foundation for the network of political confidence in the administration. As a result, it's critical to establish public trust so that people can comprehend the e-government implementation process and increase government accountability.Di era digital saat ini, internet adalah kebutuhan yang sangat penting. Tata kelola pemerintahan lokal seperti yang saat ini dipraktikkan sepenuhnya didasarkan pada teknologi digital. Program Internet Masuk RT dikembangkan untuk memajukan sumber daya manusia masyarakat Ponorogo. Artikel ini mengkaji kesiapan e-government untuk mengelola program Internet Masuk RT dan mengeksplorasi bagaimana hal itu telah mempengaruhi anggota Muhammadiyah di Ponorogo. Pendekatan kuantitatif digunakan dalam melakukan penelitian ini. Masyarakat Muhammadiyah Ponorogo menerima kuesioner tersebut. Data diolah menggunakan PLS SEM dan dilakukan analisis deskriptif kuantitatif. Temuan penelitian menunjukkan bahwa 95% kesiapan e-government telah tercapai, khususnya di bidang infrastruktur TIK, hukum dan peraturan, lingkungan sosial, pekerjaan manajerial, kepemimpinan, kompetensi tenaga kerja, dan keamanan informasi. Dengan mewujudkan kesiapan e-government dalam program Internet Masuk RT, mendorong kepercayaan publik. Kepercayaan publik terhadap e-government berfungsi sebagai fondasi bagi jaringan kepercayaan politik dalam pemerintahan. Oleh karena itu, sangat penting untuk membangun kepercayaan publik sehingga masyarakat dapat memahami proses implementasi e-government dan meningkatkan akuntabilitas pemerintah.